1996
DOI: 10.1016/s0896-6273(00)80028-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of Charge Movement in Voltage-Gated Sodium Channels

Abstract: Voltage-dependent movement of a sodium channel S4 segment was examined by cysteine scanning mutagenesis and testing accessibility of the residues to hydrophilic cysteine-modifying reagents. These experiments indicate that 2 charged S4 residues move completely from an internally accessible to an externally accessible location in response to depolarization by passage through a short "channel" in the protein. The energetic problems of S4 movement have thus been solved in the same way that may ion channels achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
511
3
3

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 578 publications
(558 citation statements)
references
References 39 publications
41
511
3
3
Order By: Relevance
“…S5 and S6 in each domain are connected via a P (pore)-segment that lines the outer pore of the ion channel [Fozzard and Hanck, 1996]. Three fundamental gating processes characterize the Na v 1.5 channel [Yang et al, 1996]: activation, fast inactivation, and slow inactivation. Activation is a process whereby the channel opens and Na 1 enters the cell; it is the basic biophysical process behind the cardiac depolarization.…”
Section: Brs1-mutations In Scn5amentioning
confidence: 99%
“…S5 and S6 in each domain are connected via a P (pore)-segment that lines the outer pore of the ion channel [Fozzard and Hanck, 1996]. Three fundamental gating processes characterize the Na v 1.5 channel [Yang et al, 1996]: activation, fast inactivation, and slow inactivation. Activation is a process whereby the channel opens and Na 1 enters the cell; it is the basic biophysical process behind the cardiac depolarization.…”
Section: Brs1-mutations In Scn5amentioning
confidence: 99%
“…Moreover, in this Ca 2+ concentration interval, the channel can be maximally activated by voltage, indicating that in the absence of Ca 2+ , voltages high enough can increase the P o to its maximum value . In voltage-dependent channels, membrane depolarization promotes the displacement of the charged residues contained in the S4-inducing gating currents (Armstrong and Bezanilla, 1973;Schneider and Chandler, 1973;Keynes and Rojas, 1974;Yang and Horn, 1995;Aggarwal and MacKinnon, 1996;Seoh et al, 1996;Larsson et al, 1996;Yang et al, 1996;Yusaf et al, 1996;Ahern and Horn, 2004). Gating currents in BK channels were detected by Stefani et al, (1997) in the absence of Ca 2+ and showed that like the G(V) curves, the gating charge-voltage (Q(V)) curves were left-shifted in the presence of Ca 2+ .…”
Section: Sensing Elementsmentioning
confidence: 99%
“…The voltage sensitivity of these channels is derived from a transmembrane ␣-helical segment that contains a cluster of four to eight positively charged amino acids (lysine or arginine). The charged residues form a dipole that moves outward in response to membrane depolarization 7,8 and thereby influences the probability of adopting the closed or open conformation. This cluster of positive charges is in the so-called S4-segment, the fourth of six membranespanning segments in the canonical architecture of a channel subunit in the voltage-gated superfamily (FIG.…”
Section: Voltage-gated Ion Channelsmentioning
confidence: 99%